2016
DOI: 10.1002/2016ja022797
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐scale gravity wave activity in the thermosphere inferred from GOCE data

Abstract: This study is focused on the effect of solar flux conditions on the dynamics of gravity waves (GWs) in the thermosphere. Air density and crosswind in situ estimates from the Gravity Field and Steady‐State Ocean Circulation Explorer (GOCE) accelerometers are analyzed for the whole mission duration. The analysis is performed in the Fourier spectral domain averaging spectral results over periods of 2 months close to solstices. A new GW marker (called Cf3) is introduced here to characterize GWs activity under low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Here we discuss why the TEC variation and the GW activity are weaker in summer (SH) than that in winter (NH). The model study by Miyoshi et al () and the observational study by Forbes et al () and Garcia et al () demonstrated that the GW activity at middle and high latitudes in the thermosphere is stronger in winter than in summer. From these results, there are two plausible candidates for the seasonal difference in the GW activity.…”
Section: Discussionmentioning
confidence: 96%
“…Here we discuss why the TEC variation and the GW activity are weaker in summer (SH) than that in winter (NH). The model study by Miyoshi et al () and the observational study by Forbes et al () and Garcia et al () demonstrated that the GW activity at middle and high latitudes in the thermosphere is stronger in winter than in summer. From these results, there are two plausible candidates for the seasonal difference in the GW activity.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the dynamical forcing, GWs contribute to heating and cooling of the thermosphere above the turbopause (∼105 km) up to F 2 layer altitudes, reaching peak values of ∼170 K d −1 [ Yiğit and Medvedev , ]. Since the thermosphere is strongly susceptible to variations of solar activity, GW propagation and effects exhibit appreciable changes, as was predicted by general circulation models (GCMs) [ Yiğit and Medvedev , ] and recently demonstrated by satellite observations [ Park et al , ; Garcia et al , ]. Transient events in the lower and middle atmosphere, such as sudden stratospheric warmings, also alter propagation of GWs causing an increase of the GW activity in the upper thermosphere by more than a factor of 3 [ Yiğit and Medvedev , , ] and generating changes in the thermospheric circulation up to ±50% [ Yiğit et al , ].…”
Section: Introductionmentioning
confidence: 95%
“…For the T/I region thus dedicated experimental evidence is needed to compare GW distributions in the middle atmosphere and in the T/I. Until recently, several observational studies of GWs in the T/I have been performed (e.g., Bruinsma and Forbes, 2008;Park et al, 2014;Forbes et al, 2016;Garcia et al, 2016). In particular, Park et al (2014) derived global GW distribution using CHAMP mass density and performed a first comparison with a global distribution of GW temperature variances in the stratosphere.…”
Section: Q T Trinh Et Al: Satellite Observations Of Vertical Couplmentioning
confidence: 99%